A precursor-derived nanocrystalline boron carbide-based composite ceramic and a superhigh-pressure preparation method thereof
Patent Information
- Application Number
- CN202611089422.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-22
- Publication Date
- 2026-10-16
AI Technical Summary
这不仅解决了碳化硼陶瓷韧性低的难题,同时利用超高压制备高致密纳米/非晶结构碳化硼陶瓷,弥补现有晶体结构中子吸收材料耐辐照性能差的问题,有望从根本上解决碳化硼辐照性能低的难题
(1)断裂韧性提升。利用特定碳化硼前驱体衍生粉体获得纳米晶-非晶碳化硼,在超高压下低温烧结可维持纳米晶粒尺寸,抑制晶粒长大,从而提高陶瓷的断裂韧性和各项性能。
Smart Images

Figure CN122916677A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of advanced structural ceramics and nuclear neutron absorbing ceramic materials, specifically relating to a nanocrystalline boron carbide-based composite ceramic and its preparation method that utilizes the synergistic regulation of precursor phase, particle interface and ultra-high pressure thermal process. Background Technology
[0002] Boron carbide is a commonly used neutron absorbing material because of its isotopes. 10 B has an extremely high neutron absorption cross section (4020 Barn). 10 Boron carbide absorbers do not produce radioactive isotopes after absorbing neutrons, produce low-energy secondary radiation, and are characterized by high hardness, good corrosion resistance, and stable thermal properties. They are primarily used in Russian water reactors. Boron carbide absorbers, on the other hand, exhibit a rapid decrease in absorption value with fuel burnup and are prone to severe radiation damage. This is mainly because… 10 The (n,α) reaction of B releases a large amount of helium gas, causing the B4C core to swell, which can easily lead to bulging and damage of the cladding tube.
[0003] To address the above issues, scholars have conducted numerous studies. CN102757223A investigated composite materials of rare earth compounds and boron carbide, aiming to solve the problem of low combustion value of boron carbide. CN114292108A studied the addition of gadolinium oxide for mixed sintering, resulting in a sintered body that maintains thermal conductivity while possessing a certain degree of porosity to accommodate helium gas generated after boron carbide absorbs neutrons, thus reducing irradiation swelling rate. CN111116203A disclosed the preparation of boron carbide nano-ceramics by mixing nano-boron carbide or nano-carbon materials with amorphous boron and then sintering at 3–6 GPa and 1300–1600℃ for a short time. This scheme demonstrates that GPa-level pressure can promote densification of nano-boron carbide, but it does not address the precursor-derived amorphous nano-boron carbide state, nor does it address the post-sintering interface structure of low-content coated diamond in this system. CN118754694A discloses a boron carbide composite bulletproof material containing 10wt%~30wt% diamond, sintered using SPS at 40~50 MPa. The above schemes address second-phase reinforcement and rare-earth neutron absorption, respectively, but do not solve the problem of simultaneously achieving high densification, nanocrystal retention, and stable interface toughening during GPa-level rapid sintering of precursor-derived boron carbide. Furthermore, most studies balance and adjust the reactivity of boron carbide ceramics by doping with rare earth elements, but none fundamentally solve the problem of irradiation swelling in boron carbide used as a neutron-absorbing material. Summary of the Invention
[0004] To address the aforementioned problems, the present invention aims to provide a precursor-derived nanocrystalline boron carbide-based composite ceramic and its ultra-high pressure preparation method. This invention optimizes the preparation of boron carbide precursor powder to obtain nanocrystalline-amorphous boron carbide precursors. Utilizing different nanocrystalline-amorphous boron carbide precursors, diamond coating, and rare earth compound compensation design, combined with an ultra-high pressure preparation process, a highly dense precursor-derived nanocrystalline boron carbide-based composite ceramic is synthesized. Under conditions that do not rely on high diamond content or prolonged high-temperature sintering, the precursor-derived boron carbide is rapidly densified under GPa-level pressure, while simultaneously suppressing boron carbide grain coarsening and improving the diamond / boron carbide interface bonding. This not only solves the problem of low toughness in boron carbide ceramics but also utilizes ultra-high pressure to prepare highly dense nanocrystalline / amorphous boron carbide ceramics, overcoming the poor radiation resistance of existing crystalline neutron-absorbing materials, and is expected to fundamentally solve the problem of low radiation performance of boron carbide.
[0005] In a first aspect, the present invention provides a method for preparing precursor-derived nanocrystalline boron carbide-based composite ceramics under ultra-high pressure. The preparation method includes the following steps: (1) Preparation of precursor-derived powders containing amorphous boron carbide and nano boron carbide; (2) Weigh the raw materials according to the following mass percentages, of which 0.1%~5% is diamond, 0.1%~20% is rare earth oxide, 0.2%~2% is sintering aid, and the remainder is precursor-derived powder containing amorphous boron carbide and nano boron carbide. The sum of the mass percentages of each component is 100%. Mix the raw materials to obtain mixed powder. (3) Press the mixed powder obtained in step (2) into a blank; (4) Pressurize the green body obtained in step (3) to 1~6.5 GPa, and while maintaining the pressure, raise the temperature to the first sintering temperature of 800~1400℃ and hold for 0.5~60 min, then raise the temperature to the second sintering temperature of 1200~1600℃ and hold for 1~120 min. The second sintering temperature is more than 100℃ higher than the first sintering temperature. After sintering, continue to maintain the pressure and lower the temperature to the depressurization temperature. Finally, depressurize to atmospheric pressure to obtain precursor-derived nanocrystalline boron carbide-based composite ceramic. The depressurization temperature refers to the temperature of the medium in the system when the pressure in the pressure-bearing system reaches the safe release setting opening pressure. The depressurization temperature of this invention can be 700℃~room temperature.
[0006] This invention establishes interconnected technical links through identifiable precursor phases, post-sintering interface structures, and ordered hot-pressing paths. The high-density interfaces in nanocrystalline neutron-absorbing materials promote the absorption and containment of irradiation defects and the recombination of interstitial atoms and vacancies, effectively suppressing the aggregation of irradiation defects and enabling self-healing of irradiation damage. Amorphous materials are potential radiation-resistant materials, but the chaotic changes in atomic arrangement caused by irradiation are easily buried within their own disordered structure. Only nano / amorphous structures can solve the problem of boron carbide irradiation swelling and expand the applications of boron carbide ceramics.
[0007] In an optional embodiment, the rare earth oxide is selected from at least one of cerium oxide, thulium oxide, samarium oxide, gadolinium oxide, dysprosium oxide, europium oxide, and terbium oxide.
[0008] In an optional embodiment, the sintering aid is selected from at least one of carbon black, graphene, graphene oxide, carbon powder, and phenolic resin.
[0009] In optional embodiments, the diamond plating involves plating a layer of elemental titanium, a layer of elemental boron, or a layer of boron carbide onto the surface of diamond particles; preferably, the plating is performed using vacuum micro-evaporation, magnetron sputtering, vapor deposition, molten salt electrodeposition, molten salt thermal diffusion, or molten salt chemical reaction; more preferably, the thickness of the plating is 0.1~2 μm.
[0010] In an optional embodiment, the average size of the coated diamond, rare earth oxide, and sintering aid is independently 5 nm to 50 μm.
[0011] In an optional implementation, the ratio of boron source to carbon source is designed based on a B / C atomic ratio ≥ 4, and precursor-derived powders are prepared by polymer precursor pyrolysis or sol-gel method.
[0012] In an optional embodiment, the boron source is selected from one or more of amorphous boron powder, boron oxide, and boric acid, and the carbon source is selected from one or more of polyvinyl alcohol, citric acid, tartaric acid, glycerol, phenolic resin, sucrose, and ethylene glycol.
[0013] In an optional embodiment, the precursor-derived powder is prepared by mixing a boron source and a carbon source according to a designed atomic ratio, drying and curing, then carbonizing at low temperature in an inert atmosphere, and then reacting at high temperature in an inert atmosphere to obtain the precursor-derived powder.
[0014] In an optional embodiment, during ultra-high pressure sintering, the pressure is first increased to a sintering pressure of 1-6.5 Gpa at a rate of 0.3-0.5 GPa / min. Then, while maintaining the pressure, the temperature is increased to a first sintering temperature of 800-1400°C at a rate of 30-60°C / s and held for 0.5-60 min. Next, the temperature is increased to a second sintering temperature of 1200-1600°C within 30-120 s and held for 1-120 min. After sintering, while maintaining the pressure, the temperature is decreased to 500-700°C at a rate of 15-30°C / s and held for 5-8 min before natural cooling to room temperature. Finally, the pressure is decreased to atmospheric pressure at a rate of 0.1-0.6 GPa / min.
[0015] In a second aspect, the present invention provides precursor-derived nanocrystalline boron carbide-based composite ceramics obtained according to the preparation method described in any one of the preceding claims.
[0016] Compared with the prior art, the present invention has the following beneficial effects: (1) Improved fracture toughness. Nanocrystalline-amorphous boron carbide is obtained by using specific boron carbide precursor-derived powders. Low-temperature sintering under ultra-high pressure can maintain the nanocrystal size and inhibit grain growth, thereby improving the fracture toughness and various properties of the ceramic.
[0017] (2) Radiation resistance is expected to improve. Diamond SP 3 The hybrid C / C bond has a high binding energy and a strong lattice bond, resulting in strong radiation resistance. Even under high-dose, high-energy particle irradiation, its lattice mismatch is very small. Meanwhile, diamond's high band gap of 5.47 eV also signifies its superior radiation resistance. Doping boron carbide ceramics with rare earth elements and diamond in the composition design holds promise for improving their radiation resistance.
[0018] (3) Compared with conventional sintering in the prior art, this invention utilizes an ultra-high pressure process to prepare boron carbide ceramics, thereby reducing the sintering temperature and achieving rapid densification of the material. Simultaneously, it refines the microstructure, suppresses grain nucleation, precipitation, and growth, and yields nanocrystalline / amorphous boron carbide ceramics. The large and small angle grain boundaries, phase boundaries, and other interface structures in the nanocrystalline / amorphous boron carbide ceramics can act as traps, capturing and eliminating irradiation defects such as interstitial atoms, voids, and helium bubbles, which is expected to improve the radiation damage resistance of boron carbide.
[0019] (4) Compared with the single-stage sintering, uncoated diamond and commercially available nano boron carbide powder with the same peak temperature and total holding time, the precursor-derived nanocrystalline boron carbide-based composite ceramic obtained by the method of the present invention can improve the relative density, grain size and fracture toughness under the same test conditions. Attached Figure Description
[0020] To more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly described below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0021] Figure 1 This is an exemplary high-temperature and high-pressure assembly diagram of the present invention, wherein 1-pyrophyllite; 2-dolomite tube; 3-steel ring; 4-boron nitride tube; 5-carbon tube; 6-sample; 7-magnesium oxide sheet; 8-molybdenum sheet; 9-carbon sheet.
[0022] Figure 2 This is a cross-sectional scanning electron microscope (SEM) image of the precursor-derived nanocrystalline boron carbide-based composite ceramic of Example 1. It can be seen that the ceramic grain size is at the nanometer level.
[0023] Figure 3 The image shows the XRD patterns of the precursors containing amorphous boron carbide and nano boron carbide from Example 1.
[0024] Figure 4 The image shows scanning electron microscope (SEM) images of the precursors containing amorphous boron carbide and nano-boron carbide from Example 1. (Combined with...) Figure 3 and Figure 4 It can be seen that amorphous boron carbide and nanocrystalline boron carbide coexist in the boron carbide precursor. Detailed Implementation
[0025] The present invention is further illustrated by the following embodiments. It should be understood that the following embodiments are for illustrative purposes only and are not intended to limit the present invention.
[0026] Currently, the preparation of amorphous boron carbide is mainly in the field of thin films or coatings, employing non-equilibrium techniques such as physical or chemical vapor deposition. These methods rapidly deposit atoms on a low-temperature substrate with extremely fast cooling rates, preventing atoms from arranging themselves into a long-range ordered structure, thus directly forming an amorphous structure. Conventional pressureless sintering and hot pressing are difficult to use for preparing amorphous boron carbide ceramics. The core reason is that the nature and goals of these two processes are completely contradictory to the conditions required to maintain the amorphous state of the material. The purpose of pressureless sintering and hot pressing is to induce atomic migration and rearrangement through high temperatures (usually 1900~2300°C) and pressure, sintering loose powder into dense crystalline ceramics with highly ordered atomic arrangement to obtain excellent mechanical properties. However, the amorphous state is thermodynamically unstable; its atomic structure is long-range disordered. To obtain and maintain this state, extremely rapid cooling rates are required to freeze the disordered structure at high temperatures, preventing atoms from having time to arrange themselves into ordered crystals. However, conventional pressureless and hot-pressing sintering requires prolonged high-temperature holding to achieve densification. This provides ample time and energy for atomic diffusion and ordered arrangement to form crystals. Under these conditions, the material will inevitably crystallize rather than remain amorphous. Therefore, in conventional sintering methods, amorphous boron carbide precursors tend to crystallize completely and cannot maintain an amorphous state.
[0027] The following exemplifies the precursor-derived nanocrystalline boron carbide-based composite ceramics and their ultra-high pressure preparation method.
[0028] A mixed powder is obtained by mixing coated diamond, boron carbide precursor (also known as precursor-derived powder), rare earth oxides, and sintering aids. In an optional embodiment, the composition by mass percentage is: coated diamond 0.1%–5%, rare earth oxides 0.1%–20%, sintering aids 0.2%–2%, with the remainder being precursor-derived powders, and the sum of the mass percentages of the above components is 100%. In a preferred embodiment, the composition by mass percentage is: coated diamond 0.5%–5%, boron carbide precursor 75%–95%, rare earth oxides 4%–20%, and sintering aids 0.2%–2%.
[0029] A further embodiment is as follows: the coated diamond (also referred to as diamond particle coating) is prepared by depositing elemental titanium, elemental boron, or boron carbide coatings onto the surface of nanodiamond powder using vacuum micro-evaporation, magnetron sputtering, vapor deposition, or molten salt methods to obtain coated diamond particles. It should be understood that the preparation method of the coated diamond is a conventional technique in the art. In optional embodiments, the coating thickness is 0.1~2 μm. In the various embodiments and comparative examples, the particle size of the coated diamond particles is 1~3 μm, and the coating thickness is 0.1~0.2 μm.
[0030] A further option is that the boron carbide precursor is a precursor-derived powder containing amorphous boron carbide and nano-boron carbide.
[0031] A further approach is to prepare the boron carbide precursor via polymer precursor pyrolysis or sol-gel method. The ratio of boron source to carbon source is designed based on the stoichiometry of boron carbide, with a B / C atomic ratio ≥ 4. For example, a B / C atomic ratio between 4 and 10. Boron sources include, but are not limited to, amorphous boron powder, boron oxide, and boric acid. Carbon sources include, but are not limited to, polyvinyl alcohol (PVA), citric acid, tartaric acid, glycerol, phenolic resin, sucrose, and ethylene glycol (EG).
[0032] A further approach is to prepare the boron carbide precursor by drying and curing a boron source and a polymer carbon source, followed by low-temperature carbonization in an inert atmosphere and high-temperature pre-reaction. The boron source and carbon source are mixed in atomic ratios, dried and cured, then carbonized at low temperature in an inert atmosphere, and subsequently reacted at high temperature in an inert atmosphere to obtain a precursor-derived powder containing both amorphous and nano-sized boron carbide.
[0033] In optional embodiments, the drying and curing temperature is 50~200℃, and the drying and curing time is 1~16 hours. In optional embodiments, the low-temperature carbonization temperature is 200~900℃, and the low-temperature carbonization time is 0.5~12 hours. In optional embodiments, the high-temperature reaction temperature is 900~1600℃, and the high-temperature reaction time is 0.5~12 hours. The inert atmosphere includes, but is not limited to, argon.
[0034] In optional embodiments, the drying and curing temperature, the low-temperature carbonization temperature, and the high-temperature reaction temperature increase sequentially. In some embodiments, the low-temperature carbonization temperature is more than 100°C higher than the drying and curing temperature, preferably 150~750°C higher; the high-temperature reaction temperature is more than 200°C higher than the low-temperature carbonization temperature, preferably 200~1400°C higher.
[0035] A further option is that the rare earth element in the rare earth oxide is selected from at least one of Ce, Tm, Sm, Gd, Dy, Eu, and Tb compounds.
[0036] A further option is that the sintering aid is selected from at least one of carbon black, graphene, graphene oxide, carbon powder, and phenolic resin.
[0037] A further option is that the average size of the coated diamond, rare earth oxides, and sintering aids is independently 5 nm to 50 μm.
[0038] A further approach is to press the obtained mixed powder into a blank. The pressing method includes, but is not limited to, cold pressing.
[0039] A further approach is to pressurize the blank obtained in step (3) to 1~6.5 GPa, raise the temperature to the first sintering temperature of 800~1400℃ while maintaining the pressure, hold for 0.5~60 min, raise the temperature to the second sintering temperature of 1200~1600℃ and hold for 1~120 min; after sintering, lower the temperature to the depressurization temperature while maintaining the pressure, and finally depressurize to atmospheric pressure to obtain precursor-derived nanocrystalline boron carbide-based composite ceramic.
[0040] In an optional embodiment, the second sintering temperature is 100°C or more higher than the first sintering temperature; preferably, the second sintering temperature is 150-400°C higher than the first sintering temperature.
[0041] In an optional embodiment, during ultra-high pressure sintering, the pressure is first increased to a sintering pressure of 1-6.5 GPa (e.g., 2-5.8 GPa) at a rate of 0.3-0.5 GPa / min. Then, while maintaining the pressure, the temperature is increased to a first sintering temperature of 800-1400℃ at a rate of 30-60℃ / s and held for 0.5-60 min. Next, the temperature is increased to a second sintering temperature of 1200-1600℃ within 30-120 s and held for 1-120 min. After sintering, while maintaining the pressure, the temperature is decreased to 500-700℃ at a rate of 15-30℃ / s and held for 5-8 min before naturally cooling to room temperature. Finally, the pressure is decreased to atmospheric pressure at a rate of 0.1-0.6 GPa / min.
[0042] A further approach is as follows: During ultra-high pressure sintering, the pressure is first increased to a sintering pressure of 2-5.8 Gpa at a rate of 0.3-0.5 GPa / min. Then, the temperature is increased to the first sintering temperature of 1320℃ at a rate of 30-60℃ / s and held for 60s. The temperature is then increased to the second sintering temperature of 1500℃ within 30-120s and held for 30 min. After sintering, the temperature is decreased to 600℃ at a rate of 15-30℃ / s while maintaining the pressure and held for 5-8 min before naturally decreasing to room temperature. Finally, the pressure is decreased to atmospheric pressure at a rate of 0.1-0.6 GPa / min.
[0043] This invention introduces ultra-high pressure sintering to prepare precursor-derived nanocrystalline boron carbide-based composite ceramics. The mechanical force provided by high pressure can crush agglomerates in ceramic powder, promote rapid particle sliding rearrangement and plastic deformation, eliminate pores between particles, and make particles in close contact. This facilitates the bonding of surface atoms, improves the diffusion mass transfer rate, and significantly promotes the densification process during sintering, effectively alleviating the contradiction between densification sintering and microstructure control. Densification sintering of high-temperature structural ceramic materials often requires very high sintering temperatures. There is an irreconcilable contradiction between material densification, microstructure refinement, and crystallization. High pressure technology can achieve low-temperature rapid sintering. Under appropriate conditions, the effect of low temperature hindering grain nucleation can offset the effect of high pressure promoting grain nucleation, effectively alleviating the contradiction between material densification sintering and microstructure control, thereby obtaining amorphous or amorphous / nanocrystalline ceramic materials. The preparation of nano / amorphous ceramics under ultra-high pressure can fundamentally solve the problem of low radiation resistance of boron carbide, and is of great significance for preparing neutron absorbing materials with excellent comprehensive properties such as high toughness and radiation resistance.
[0044] A further approach is to place the billet in a pyrophyllite mold using a six-sided top press for ultra-high pressure sintering. It should be understood that the assembly technology of ultra-high pressure sintering is not the core innovation of this invention. See also... Figure 1Using pyrophyllite (1) as the outer pressure transmission medium matrix, a coaxial hollow cavity is prefabricated inside the pyrophyllite block. All functional components are symmetrically assembled along the central axis of the cavity, and the whole structure is double symmetrical in the upper and lower and left and right. The spatial nesting and stacking relationship of each component is as follows: Steel rings (3) are respectively assembled at the upper and lower opening ends of the pyrophyllite cavity. The steel rings directly press the end buffer sealing plates to achieve axial rigid constraint, resist the expansion deformation of the cavity end under high pressure conditions, and complete the axial locking of the overall structure. Along the axial direction from the inner side of the steel ring to the center of the cavity, molybdenum sheets (8) and carbon sheets (9) are stacked layer by layer. The arrangement order of the upper and lower ends is completely consistent: the steel ring is attached to the molybdenum sheet, and the inner side of the molybdenum sheet is tightly attached to the carbon sheet. The molybdenum sheet serves as a high-temperature resistant buffer sealing layer, and the carbon sheet has both end conductivity and axial pressure transmission functions. The two thin sheets together constitute a sealing, conductivity, and buffer composite structure at both ends of the cavity. Dolomite tubes (2) are symmetrically placed on the left and right inner walls of the pyrophyllite hollow cavity. The dolomite tubes serve as the outer sleeve for lateral heat insulation and pressure transmission. Boron nitride tubes (4) are coaxially nested inside the dolomite tubes to form a double-layer lateral heat insulation structure, which isolates the internal heating carbon tube from the outer dolomite tube, reduces heat loss, and prevents short circuits. Magnesium oxide sheets (7) are placed on the upper and lower end faces of the inner cavity of the boron nitride tube to axially limit the central carbon tube and further improve the end insulation performance. The left and right boron nitride tubes enclose the central cavity, and the carbon tube (5) resistance heating body is placed coaxially inside the cavity. The experimental sample (6) is filled into the inner cavity of the carbon tube. The sample is located at the geometric center of the entire assembly structure and is completely surrounded and wrapped by the carbon tube, which can obtain a uniform and stable temperature field and pressure field. The two ends of the carbon tube contact the upper and lower carbon sheets of the cavity to conduct current, and the sample is heated at high temperature by its own resistance. Pyrophyllite serves as the overall pressure transmitter, uniformly transferring external loads to all internal components; the steel ring provides axial rigid support; the composite sleeve of dolomite and boron nitride tubes provides lateral thermal insulation; the carbon tube and carbon sheets at both ends form a heating circuit, providing a high-temperature environment; the molybdenum sheet enhances the end sealing and buffering effect, and the magnesium oxide sheet achieves axial positioning and insulation isolation of the carbon tube; the sample is placed in the center of the cavity, in the core area where pressure and temperature are most uniform. During assembly, dolomite tubes are first embedded into the left and right side walls of the pyrophyllite prefabricated cavity, and boron nitride tubes are coaxially nested and magnesium oxide sheets are placed to complete the positioning; then, carbon tubes are installed inside the boron nitride tubes, and the sample is filled into the hollow inner cavity of the carbon tubes; carbon sheets and molybdenum sheets are laid sequentially at the upper and lower openings of the cavity, and finally, the steel ring is pressed in and locked for sealing. All components are arranged coaxially to form a sealed integrated high-temperature and high-pressure experimental cavity.
[0045] This invention also provides the application of boron carbide ceramics prepared by the above-mentioned method for preparing precursor-derived nanocrystalline boron carbide-based composite ceramics in structural ceramics, functional ceramics, and nuclear fields. In the nuclear field, applications include, but are not limited to, control of nuclear reactivity and nuclear radiation shielding.
[0046] In summary, this invention relates to a precursor-derived nanocrystalline boron carbide-based composite ceramic and its ultra-high pressure preparation method. This method utilizes boron carbide precursor-derived powder, diamond coating, rare earth compound compensation design, and an ultra-high pressure preparation process to synthesize highly dense, precursor-derived nanocrystalline boron carbide-based composite ceramics. This not only solves the problem of low toughness in boron carbide ceramics but also utilizes ultra-high pressure to prepare highly dense nano / amorphous boron carbide ceramics, overcoming the poor radiation resistance of existing crystalline neutron-absorbing materials and potentially fundamentally solving the problem of boron carbide radiation swelling.
[0047] The following examples further illustrate the present invention in detail. It should also be understood that the following examples are only for further explanation of the present invention and should not be construed as limiting the scope of protection of the present invention. Any non-essential improvements and adjustments made by those skilled in the art based on the above description of the present invention are within the scope of protection of the present invention. The specific process parameters, etc., in the following examples are merely examples within a suitable range; that is, those skilled in the art can make appropriate selections within the appropriate range based on the description herein, and are not intended to be limited to the specific values in the examples below.
[0048] The fracture toughness of boron carbide-based composite ceramics was determined by indentation method according to standard ISO 21618:2025.
[0049] Example 1
[0050] The preparation method of precursor-derived nanocrystalline boron carbide-based composite ceramics includes the following steps: Step (1): Preparation of precursor-derived powder containing amorphous boron carbide and nano boron carbide. Amorphous boron powder and polyvinyl alcohol were mixed at a B / C atomic ratio of 5:1. The resulting mixture was dried and cured at 50°C for 8 hours, then carbonized at 200°C for 4 hours under an argon inert atmosphere, and subsequently reacted at 1400°C for 2 hours under an argon inert atmosphere to obtain precursor-derived powder containing amorphous boron carbide and nano boron carbide.
[0051] Step (2): Weigh boron-plated diamond, precursor-derived powder containing amorphous boron carbide and nano boron carbide, rare earth oxides, and phenolic resin according to the specified proportions. By mass percentage, 0.5% boron-plated diamond, 95% precursor-derived powder containing amorphous boron carbide and nano boron carbide, 2% dysprosium oxide, 2% terbium oxide, and 0.5% phenolic resin are used as raw materials. These raw materials are then mixed to obtain a mixed powder.
[0052] Step (3): Cold press the mixed powder obtained in step (2) into a blank.
[0053] Step (4): Place the blank obtained in step (3) into a pyrophyllite mold for a six-sided press. First, pressurize it to a sintering pressure of 5.8 GPa at a pressurization rate of 0.3 GPa / min. Then, under pressure holding conditions, heat it to the first sintering temperature of 1320℃ at a heating rate of 30℃ / s and hold it for 20 min. Then, within 30 s, heat it to the second sintering temperature of 1500℃ and hold it for 30 min. After sintering, continue to hold the pressure and cool it down to 600℃ at a rate of 15℃ / s and hold it for 5 min before letting it cool down to room temperature. Finally, reduce the pressure to atmospheric pressure at a rate of 0.1 GPa / min to obtain precursor-derived nanocrystalline boron carbide-based composite ceramic.
[0054] Testing revealed that the boron carbide ceramic prepared in Example 1 had a relative density of 98.6%, a grain size of 80–100 nm, and a fracture toughness of 8.21 MPa·m. 1 / 2 .
[0055] Example 2
[0056] The preparation method of precursor-derived nanocrystalline boron carbide-based composite ceramics includes the following steps: Step (1): Preparation of precursor-derived powder containing amorphous boron carbide and nano boron carbide. Boric acid and sucrose were mixed at a B / C atomic ratio of 6:1. The resulting mixture was dried and cured at 200°C for 1 hour, then carbonized at 800°C for 4 hours under an argon inert atmosphere, and subsequently reacted at 1000°C for 2 hours under an argon inert atmosphere to obtain precursor-derived powder containing amorphous boron carbide and nano boron carbide.
[0057] Step (2): Weigh the boron carbide-plated diamond, precursor-derived powder containing amorphous boron carbide and nano-boron carbide, rare earth oxides, and carbon black according to the specified proportions. By mass percentage, use 5% boron carbide-plated diamond, 75% precursor-derived powder containing amorphous boron carbide and nano-boron carbide, 18% dysprosium oxide, and 2% carbon black as raw materials. Mix these raw materials to obtain a mixed powder.
[0058] Step (3): Cold press the mixed powder obtained in step (2) into a blank.
[0059] Step (4): Place the blank obtained in step (3) in a pyrophyllite mold for a six-sided press. First, pressurize it to a sintering pressure of 2 GPa at a pressurization rate of 0.5 GPa / min. Then, under pressure holding conditions, heat it to the first sintering temperature of 1350℃ at a heating rate of 60℃ / s and hold it for 30 min. Then, within 120 s, heat it to the second sintering temperature of 1550℃ and hold it for 120 min. After sintering, continue to hold the pressure and cool it down to 600℃ at a rate of 30℃ / s and hold it for 8 min. Then, let it cool down to room temperature naturally. Finally, reduce the pressure to atmospheric pressure at a rate of 0.6 GPa / min to obtain precursor-derived nanocrystalline boron carbide-based composite ceramic.
[0060] Testing revealed that the boron carbide ceramic prepared in Example 2 had a relative density of 96.8%, a grain size of 200–240 nm, and a fracture toughness of 5.26 MPa·m. 1 / 2 .
[0061] Example 3
[0062] The preparation method of precursor-derived nanocrystalline boron carbide-based composite ceramics includes the following steps: Step (1): Preparation of precursor-derived powder containing amorphous boron carbide and nano-boron carbide. Boron oxide and ethylene glycol were mixed at an atomic ratio of 4:1. The resulting mixture was dried and cured at 150°C for 2 hours, then carbonized at 900°C for 6 hours under an argon inert atmosphere, and subsequently reacted at 1200°C for 3 hours under an argon inert atmosphere to obtain precursor-derived powder containing amorphous boron carbide and nano-boron carbide.
[0063] Step (2): Weigh the precursor-derived powder containing amorphous boron carbide and nano-boron carbide, titanium-plated diamond, rare earth oxides, and graphene according to the specified proportions. The raw materials are: 85% precursor-derived powder containing amorphous boron carbide and nano-boron carbide, 1% titanium-plated diamond, 6.5% dysprosium oxide, 7% gadolinium oxide, and 0.5% graphene. Mix these raw materials to obtain a mixed powder.
[0064] Step (3): Press the mixed powder obtained in step (2) into a blank.
[0065] Step (4): Place the blank obtained in step (3) in a pyrophyllite mold for a six-sided press. First, pressurize it to a sintering pressure of 4 GPa at a pressurization rate of 0.4 GPa / min. Then, while maintaining the pressure, heat it to the first sintering temperature of 800℃ at a heating rate of 50℃ / s and hold it for 60 min. Then, within 60 s, heat it to the second sintering temperature of 1200℃ and hold it for 10 min. After sintering, continue to maintain the pressure and cool it down to 600℃ at a heating rate of 20℃ / s and hold it for 6 min. Then, let it cool down to room temperature naturally. Finally, reduce the pressure to atmospheric pressure at a depressurization rate of 0.4 GPa / min to obtain precursor-derived nanocrystalline boron carbide-based composite ceramic.
[0066] The tests showed that the boron carbide ceramic prepared in Example 3 had a relative density of 95.2%, a grain size of 100-120 nm, and a fracture toughness of 6.51 MPa·m. 1 / 2 .
[0067] Example 4
[0068] The preparation method of precursor-derived nanocrystalline boron carbide-based composite ceramics includes the following steps: Step (1): Preparation of precursor-derived powder containing amorphous boron carbide and nano boron carbide. Amorphous boron powder and polyvinyl alcohol were mixed at a B / C atomic ratio of 5:1. The resulting mixture was dried and cured at 50°C for 8 hours, then carbonized at 200°C for 6 hours under an argon inert atmosphere, and subsequently reacted at 1600°C for 2 hours under an argon inert atmosphere to obtain precursor-derived powder containing amorphous boron carbide and nano boron carbide.
[0069] Step (2): Weigh the following according to the proportions: titanium-plated diamond, precursor-derived powder containing amorphous boron carbide and nano boron carbide, rare earth oxides, carbon black, and graphene. By mass percentage, use 3% titanium-plated diamond, 80% precursor-derived powder containing amorphous boron carbide and nano boron carbide, 7% cerium oxide, 8% europium oxide, 1% carbon black, and 1% graphene as raw materials. Mix these raw materials to obtain a mixed powder.
[0070] Step (3): Cold press the mixed powder obtained in step (2) into a blank.
[0071] Step (4): Place the blank obtained in step (3) in a pyrophyllite mold for a six-sided press. First, pressurize it to a sintering pressure of 5 GPa at a pressurization rate of 0.5 GPa / min. Then, while maintaining the pressure, heat it to the first sintering temperature of 1400℃ at a heating rate of 45℃ / s and hold it for 2 min. Within 90 s, heat it to the second sintering temperature of 1600℃ and hold it for 20 min. After sintering, continue to maintain the pressure and cool it down to 600℃ at a heating rate of 25℃ / s and hold it for 7 min before letting it cool to room temperature. Finally, reduce the pressure to atmospheric pressure at a depressurization rate of 0.5 GPa / min to obtain precursor-derived nanocrystalline boron carbide-based composite ceramic.
[0072] The tests showed that the boron carbide ceramic prepared in Example 4 had a relative density of 98.5%, a grain size of 50-60 nm, and a fracture toughness of 8.87 MPa·m. 1 / 2 .
[0073] Comparative Example 1 The preparation method of precursor-derived nanocrystalline boron carbide-based composite ceramics includes the following steps: Step (1): Preparation of precursor-derived powder containing amorphous boron carbide and nano boron carbide. Amorphous boron powder and polyvinyl alcohol were mixed at a B / C atomic ratio of 5:1. The resulting mixture was dried and cured at 50°C for 8 hours, then carbonized at 200°C for 4 hours under an argon inert atmosphere, and subsequently reacted at 1600°C for 2 hours under an argon inert atmosphere to obtain precursor-derived powder containing amorphous boron carbide and nano boron carbide.
[0074] Step (2): Weigh the precursor-derived powder containing amorphous boron carbide and nano boron carbide, rare earth oxides, and carbon black according to the proportions. By mass percentage, use 80% precursor-derived powder containing amorphous boron carbide and nano boron carbide, 18% dysprosium oxide, and 2% carbon black as raw materials, and mix the raw materials to obtain a mixed powder.
[0075] Step (3): Cold press the mixed powder obtained in step (2) into a blank.
[0076] Step (4): Place the blank obtained in step (3) into a pyrophyllite mold for a six-sided press. First, pressurize it to a sintering pressure of 5.8 GPa at a pressurization rate of 0.3 GPa / min. Then, heat it to the first sintering temperature of 1300℃ at a heating rate of 30℃ / s and hold it for 20 min. Then, heat it to the second sintering temperature of 1600℃ within 30 s and hold it for 30 min. After sintering, continue to maintain the pressure and cool it down to 600℃ at a rate of 15℃ / s and hold it for 5 min before cooling it to room temperature. Finally, reduce the pressure to atmospheric pressure at a rate of 0.1 GPa / min to obtain precursor-derived nanocrystalline boron carbide-based composite ceramic.
[0077] The tests showed that the boron carbide ceramic prepared in Comparative Example 1 had a relative density of 97.2%, a grain size of 150–200 nm, and a fracture toughness of 4.62 MPa·m. 1 / 2 .
[0078] Comparative Example 2 The preparation method of precursor-derived nanocrystalline boron carbide-based composite ceramics includes the following steps: Step (1): Preparation of precursor-derived powder containing amorphous boron carbide and nano boron carbide. Amorphous boron powder and polyvinyl alcohol were mixed at a B / C atomic ratio of 5:1. The resulting mixture was dried and cured at 50°C for 8 hours, then carbonized at 200°C for 4 hours under an argon inert atmosphere, and subsequently reacted at 1600°C for 2 hours under an argon inert atmosphere to obtain precursor-derived powder containing amorphous boron carbide and nano boron carbide.
[0079] Step (2): Weigh boron-plated diamond, precursor-derived powder containing amorphous boron carbide and nano boron carbide, rare earth oxides, and phenolic resin according to the specified proportions. By mass percentage, 0.5% boron-plated diamond, 95% precursor-derived powder containing amorphous boron carbide and nano boron carbide, 2% dysprosium oxide, 2% terbium oxide, and 0.5% phenolic resin are used as raw materials. These raw materials are then mixed to obtain a mixed powder.
[0080] Step (3): Cold press the mixed powder obtained in step (2) into a blank.
[0081] Step (4): The green body obtained in step (3) is sintered in a conventional high-temperature furnace without pressure. The temperature is raised to the first sintering temperature of 1320℃ at a heating rate of 30℃ / s and held for 20 min. Then, the temperature is raised to the second sintering temperature of 1500℃ within 30 s and held for 30 min. After sintering, the temperature is lowered to 600℃ at a rate of 15℃ / s and held for 5 min before naturally cooling to room temperature to obtain precursor-derived nanocrystalline boron carbide-based composite ceramic.
[0082] The tests showed that the boron carbide ceramic prepared in Comparative Example 2 had a relative density of 93.2%, a grain size of 1.5–3 μm, and a fracture toughness of 3.51 MPa·m. 1 / 2 .
[0083] Comparative Example 3 The preparation method of boron carbide-based composite ceramics includes the following steps: Step (1): Weigh boron-plated diamond, commercial boron carbide powder (average particle size 80 nm), rare earth oxides, and phenolic resin according to the specified proportions. Using 0.5% boron-plated diamond, 95% commercial boron carbide powder, 2% dysprosium oxide, 2% terbium oxide, and 0.5% phenolic resin as raw materials by mass percentage, mix the raw materials to obtain a mixed powder.
[0084] Step (2): Cold press the mixed powder obtained in step (1) into a blank.
[0085] Step (3): Place the blank obtained in step (2) in a pyrophyllite mold for a six-sided press. First, pressurize it to a sintering pressure of 5.8 GPa at a pressurization rate of 0.3 GPa / min. Then, heat it to the first sintering temperature of 1320℃ at a heating rate of 30℃ / s and hold it for 20 min. Then, heat it to the second sintering temperature of 1500℃ within 30 s and hold it for 30 min. After sintering, continue to maintain the pressure and cool it down to 600℃ at a rate of 15℃ / s and hold it for 5 min. Then, let it cool down to room temperature naturally. Finally, reduce the pressure to atmospheric pressure at a rate of 0.1 GPa / min to obtain boron carbide-based composite ceramic.
[0086] The tests showed that the boron carbide ceramic prepared in Comparative Example 3 had a relative density of 92.1%, a grain size of 100-150 nm, and a fracture toughness of 2.87 MPa·m. 1 / 2 .
[0087] Comparative Example 4 The preparation method of precursor-derived nanocrystalline boron carbide-based composite ceramics includes the following steps: Step (1): Preparation of precursor-derived powder containing amorphous boron carbide and nano boron carbide. Amorphous boron powder and polyvinyl alcohol were mixed at a B / C atomic ratio of 5:1. The resulting mixture was dried and cured at 50°C for 8 hours, then carbonized at 200°C for 4 hours under an argon inert atmosphere, and subsequently reacted at 1600°C for 2 hours under an argon inert atmosphere to obtain precursor-derived powder containing amorphous boron carbide and nano boron carbide.
[0088] Step (2): Weigh out pure diamond powder, precursor-derived powder containing amorphous boron carbide and nano boron carbide, rare earth oxides, and phenolic resin according to the specified proportions. Using 0.5% pure diamond powder, 95% precursor-derived powder containing amorphous boron carbide and nano boron carbide, 2% dysprosium oxide, 2% terbium oxide, and 0.5% phenolic resin as raw materials, mix the raw materials to obtain a mixed powder.
[0089] Step (3): Cold press the mixed powder obtained in step (2) into a blank.
[0090] Step (4): Place the blank obtained in step (3) in a pyrophyllite mold for a six-sided press. First, pressurize it to a sintering pressure of 5.8 GPa at a pressurization rate of 0.3 GPa / min. Then, heat it to the first sintering temperature of 1320℃ at a heating rate of 30℃ / s and hold it for 20 min. Then, heat it to the second sintering temperature of 1500℃ within 30 s and hold it for 30 min. After sintering, continue to maintain the pressure and cool it down to 600℃ at a rate of 15℃ / s and hold it for 5 min. Then, cool it down to room temperature naturally and reduce the pressure to atmospheric pressure at a rate of 0.1 GPa / min to obtain precursor-derived nanocrystalline boron carbide-based composite ceramic.
[0091] The tests showed that the boron carbide ceramic prepared in Comparative Example 4 had a relative density of 95.2%, a grain size of 250–300 nm, and a fracture toughness of 4.35 MPa·m. 1 / 2 .
[0092] Although the present invention has been described in detail through the preferred embodiments above, it should be understood that the above description should not be considered as a limitation of the present invention. Various modifications and substitutions to the present invention will be apparent to those skilled in the art after reading the above description. Therefore, the scope of protection of the present invention should be defined by the appended claims.
Claims
1. A method for preparing precursor-derived nanocrystalline boron carbide-based composite ceramics under ultra-high pressure, characterized in that, The preparation method includes the following steps: (1) Preparation of precursor-derived powders containing amorphous boron carbide and nano boron carbide; (2) Weigh the raw materials according to the following mass percentages, of which 0.1%~5% is diamond, 0.1%~20% is rare earth oxide, 0.2%~2% is sintering aid, and the remainder is precursor-derived powder containing amorphous boron carbide and nano boron carbide. The sum of the mass percentages of each component is 100%. Mix the raw materials to obtain mixed powder. (3) Press the mixed powder obtained in step (2) into a blank; (4) Press the green body obtained in step (3) to 1~6.5 GPa, and while maintaining the pressure, heat it to the first sintering temperature of 800~1400℃ and hold it for 0.5~60 min. Then heat it to the second sintering temperature of 1200~1600℃ and hold it for 1~120 min. The second sintering temperature is more than 100℃ higher than the first sintering temperature. After sintering, while maintaining the pressure, cool it down to the depressurization temperature and finally depressurize it to atmospheric pressure to obtain precursor-derived nanocrystalline boron carbide-based composite ceramic.
2. The preparation method according to claim 1, characterized in that, The rare earth oxide is selected from at least one of cerium oxide, thulium oxide, samarium oxide, gadolinium oxide, dysprosium oxide, europium oxide, and terbium oxide.
3. The preparation method according to claim 1 or 2, characterized in that, The sintering aid is selected from at least one of carbon black, graphene, graphene oxide, carbon powder, and phenolic resin.
4. The preparation method according to any one of claims 1 to 3, characterized in that, The diamond plating involves depositing a layer of elemental titanium, elemental boron, or boron carbide onto the surface of diamond particles. Preferably, the plating is deposited on the surface of diamond particles using vacuum micro-evaporation, magnetron sputtering, vapor deposition, molten salt electrodeposition, molten salt thermal diffusion, or molten salt chemical reaction. More preferably, the thickness of the plating is 0.1~2μm.
5. The preparation method according to any one of claims 1 to 4, characterized in that, The average size of the coated diamond, rare earth oxides, and sintering aids is independently 5 nm to 50 μm.
6. The preparation method according to any one of claims 1 to 5, characterized in that, Based on a B / C atomic ratio ≥ 4, the ratio of boron source to carbon source is designed, and precursor-derived powders are prepared by polymer precursor pyrolysis or sol-gel method.
7. The preparation method according to claim 6, characterized in that, The boron source is selected from one or more of amorphous boron powder, boron oxide, and boric acid, and the carbon source is selected from one or more of polyvinyl alcohol, citric acid, tartaric acid, glycerol, phenolic resin, sucrose, and ethylene glycol.
8. The preparation method according to claim 6 or 7, characterized in that, The method for preparing the precursor-derived powder is as follows: a boron source and a carbon source are mixed according to a designed atomic ratio, dried and cured, then carbonized at low temperature in an inert atmosphere, and subsequently reacted at high temperature in an inert atmosphere to obtain the precursor-derived powder.
9. The preparation method according to any one of claims 1 to 8, characterized in that, During ultra-high pressure sintering, the pressure is first increased to a sintering pressure of 1-6.5 Gpa at a rate of 0.3-0.5 GPa / min. Then, while maintaining the pressure, the temperature is increased to the first sintering temperature of 800-1400°C at a rate of 30-60°C / s and held for 0.5-60 min. Next, the temperature is increased to the second sintering temperature of 1200-1600°C within 30-120 s and held for 1-120 min. The second sintering temperature is more than 100°C higher than the first sintering temperature. After sintering, while maintaining the pressure, the temperature is decreased to 500-700°C at a rate of 15-30°C / s and held for 5-8 min before natural cooling to room temperature. Finally, the pressure is decreased to atmospheric pressure at a rate of 0.1-0.6 GPa / min.
10. The precursor-derived nanocrystalline boron carbide-based composite ceramic obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Rare-earth boride / boron carbide composite neutron absorption material and preparation method thereof
CN102757223A
Preparation method of high-density nano boron carbide ceramic material
CN111116203A
Boron carbide-gadolinium oxide neutron absorber material for control rod and preparation method of boron carbide-gadolinium oxide neutron absorber material
CN114292108A
Preparation method of boron carbide / diamond composite bulletproof material
CN118754694A